(untitled) (The Macau Ricci Institute Journal, 2023)
The Macau Manifesto identifies three platforms for change that can “contribute to the paradigmatic shift in economics that is already happening”: i) Subsidiarity Economics; ii) Wellbeing for All; and iii) Common Good Entrepreneurship. Following the logic of the civil economics paradigm (Becchetti-Cermelli, 2018), my belief is that “Wellbeing for All” needs to be measured by creating a new set of wellbeing indicators where value is, beyond GDP, the stock of cultural, environmental, spiritual and economic resources that a community can enjoy. To this purpose the most recent studies have developed multidimensional wellbeing and “generativity in act” indicators that provide different measures of economic, social and demographic generativity.